Ответы и объяснения

2013-12-25T11:45:18+04:00
Лучший Ответ!
2013-12-25T11:45:52+04:00
7/13*(-26/14)= -7*26/13*14= - 1*2/1*2= - 2/2= - 1/1= -1

-1/4*1 1/7*(-3 1/3)=-1/4*8/7*(-10/3)=-1*8/4*7*(-10/3)=-1*2/1*7*(-10/3)=-2/7*(-10/3)=2*10/7*3=20/21

(1/3-1 1/4)*(3/5+1/4)=(1/3-5/4)*(3*4+1*3/20)=(1*4-5*3/12)*(12+3/20)=(4-14/12)*(15/20)=(-10/12)*(3/4)=(-5/6)*3/4= - 5*3/6*4= - 5*1/2*4= - 5/8

5+0,75-5,75+4/5=5,75-5,75+4/5=0+4/5=4/5

4/7*(-7/4)*12,773= - 4*7/7*4*12,773= - 1*1/1*1*12,773= - 1*12,773=-12,773

(3 1/3+1/4)*(-3/7-1/4)=(10/3+1/4)*(-3*4-1*7/28)=(10*4+1*3/12)*(-12-7/28)=(40+3/12)*(-19/28)=43/12*(-19/28)= - 43*19/12*28= -817/336= -2 целих 145/336

13/15*30/26*(-1)*12/17=13*30/15*26*(-1)*12/17=1*2/1*2*(-1)*12/171*1/1*1*(-1)*12/17=1*(-1)*12/17=-1*12/17=-12/17